TRAINING OF WRESTLERS AT THE INITIAL STAGE OF TRAINING (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The effectiveness of training sports reserves in sports wrestling was analyzed. Especially the issue of training wrestlers at the initial stage of long-term training, on which the foundation of the wrestler's general physical training is laid, and which largely determines further successes in sports.